Edukasi Pencegahan Cacingan pada Anak di Puskesmas Simpur Kota Bandar Lampung - Dewi Kusumaningsih; Muhammad Rafli; Ilham Agung Sakti; Putri Yolanda Utama; Ni Luh Sumo; Novindri Ryalita; Mahda Rizka Faer Rifa’ie; Sumarni Sumarni; Yanti Fitria (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The number of infectious diseases is still very high in Indonesia. The World Health Organization (WHO) estimates that around 2 billion people worldwide suffer from parasitic worms, which are most common in tropical and subtropical areas and areas with poor sanitation. The number of schoolchildren infected with worms in Europe is estimated at more than 4 million, with the highest prevalence in Central and South Asian countries. In general, the prevalence of worms in Indonesia is still high, ranging between 2.5% and 62%. This high prevalence is due to the fact that Indonesia is a country with a tropical and humid climate. The aim of this activity is to increase parents' knowledge regarding preventing worms in children. Socialization methods in the form of lectures and questions and answers are used in this activity using leaflets as media. Activity Results: Respondents were very enthusiastic about the material presented and there were several respondents who asked questions. The conclusion of this educational activity was successfully carried out to increase parents' knowledge and awareness regarding preventing worms in children.